Representações sociais sobre a formação de atitudes e valores na prática pedagógica de docentes de engenharia civil da UEFS - Oliveira, Marcus Solon Sá de (2022)
This dissertation is the result of an empirical research, of a qualitative nature, developed in the Graduate Program in Education at the State University of Feira de Santana (UEFS), whose general objective was to understand, through the representations of students and teachers, how training occurs of attitudes and values ​​in the educational practice of professors of the Civil Engineering course at UEFS. The theoretical framework was based on Zabala (1998), Postic (1990), Zabalza (2000), Bolivar (2000), Rodrigues (1991), Moreno (2005), Trillo (2000), Puig (2007) and Masetto (2012) , between others. The methodology used is based on the epistemological principles of the emerging paradigm (SOUSA SANTOS, 2010), and qualitative research (MINAYO, 2007), in dialogue with the theory of social representations (MOSCOVICI, 2003; JODELET, 2001, 2005; ABRIC, 2000, 2002). As devices for data production, we used the free word association technique (TALP) and semi-structured interviews with stimulus questions. 184 students enrolled in curricular components from the 2nd to the 10th semester of the Civil Engineering course at UEFS participated in the TALP. And from the interviews with stimulus questions, eight students and eight professors. The analysis of the TALP data was carried out with the help of statistics, from which a table of four houses was drawn with the elements that structured the social representations about the formation of attitudes and values ​​in the pedagogical practice. In the analysis of the discursive part, Bardin's (2011) thematic content analysis assumptions were applied. The TALP results indicate negative and positive attitudes: archaism, lack of empathy, rigidity and demand: dedication, mastery of didactics, commitment and responsibility. The lack of empathy, rigidity and archaic teaching are attitudes of the teacher that can lead the student to emotional imbalance, lack of motivation to learn, lack of dedication to study and academic dropout, despite attitudes of commitment and responsibility of some teachers. For TALP, the results indicate negative and positive values: neglect, arrogance, egocentrism and disrespect; responsibility, honesty, mastery of didactics, professionalism, competence and excellence. Educational practice must be based on positive intentional values, focused on the quality of the teaching-learning process, for the good of all. With the results of the interviews, we organized four categories: the educational relationship; the course curriculum and the formation of attitudes and values; the teacher's reality and profile; and the reality of the class and the profile of the students. Mostly, the formation of attitudes and values ​​is congruent and positive. We also identified the different meanings attributed by teachers and students to the terms attitudes and values, and we analyzed the structure of the representations about them, which were presented as diverse, convergent and divergent. And regarding the assessment attributed by students and professors of the Civil Engineering course at UEFS to the formation of attitudes and values, its fundamental importance for the teaching-learning process and for the formation of the integral human being was perceived.